Tourist Perceptions Regarding Destination Attributes At Kelimutu Lake Area, Ende Regency: Persepsi Wisatawan Mengenai Atribut Destinasi Di Kawasan Danau Kelimutu, Kabupaten Ende - Dhiki, Katarina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to determine tourists perceptions regarding the destination attributes available at Kelimutu lake area and its surroundings. The destination attributes studied are 4A (attractions, accessibility, amenities and ancillaries). Quantitative methods were used in this research, and data was collected by distributing questionnaires to 200 respondents taken randomly. Data analysis uses quantitative descriptive techniques with the assistance of SPSS version 25 program. The results of the analysis show that tourists who visit Kelimutu Lake have a good perception toward destination attributes available in this tourist area. In other words, the destinations attributes (4A) that available around the Kelimutu lake area are considered to be good. And when the results of the analysis were examined partially for each variable, it was discovered that the attraction variable received a very good rating from tourists. Meanwhile, the other three variables, namely accessibility, amenities and ancillary, received good ratings. The results of this analysis show that Kelimutu lake has very attractive attractions for tourists. The quality of accessibility, amenities and ancillaries are also considered good by tourists. Thus, it is recommended to all stakeholders to maintain and preserve the tourist attractions they already have so that their attractiveness does not decrease or lose in the future. Apart from that, efforts are also needed to improve the quality of accessibility, amenities and ancillaries in order to increase the attractiveness of Kelimutu lake as a tourist destination.